Analysis of the Application of Technological Pedagogical Content Knowledge to the Process Learning Curriculum 2013 in Class V: Analisis Penerapan Technological Pedagogical Content Knowledge Pada Proses Pembelajaran Kurikulum 2013 di Kelas V - muhammad subhan (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
This research is motivated by the change in the curriculum of SBC into the 2013 curriculum. It has an influence on instructional technology media. Integrating learning technology, learning media and learning strategies can be done to improve the efficiency and effectiveness of learning. With these problems researchers want to know how the application of Technological Pedagogical Content Knowledge (TPACK) in the 2013 curriculum learning process in class V SDN 018 / VIII Muara Tebo.This type of research used in this study is qualitative research, the data generated is descriptive data. The subjects of this study were class V teachers, and grade V students of SDN 018 / VIII Muara Tebo. The object of this study is the application of Technological Pedagogical Content Knowledge (TPACK) in the 2013 curriculum learning process. Data collection techniques were carried out using semistructural interview methods, observation, and documentation. This type of data analysis uses the Miles & Huberman model, namely reduction, data display, conclusion drawing / verification data. The results showed that: The application of Content Knowledge (CK) in the Learning Process of the 2013 curriculum was carried out by the teacher developing student understanding in linking the content of the lesson to further learning.